Case Report: A Rare Case of a Ventricular Perivascular Epithelioid Cell Tumor With Histologic Characteristics That Resembled a Primary Cardiac Rhabdomyoma - Cossío-Aranda, Jorge; Aranda-Frausto, Alberto; Berarducci, Joaquin; Espinola-Zavaleta, Nilda; González-Melchor, Laila; Vázquez-Antona, Clara; Meléndez-Ramirez, Gabriela; Armenta-Moreno, Javier Ivan; Keirns, Candace (Frontiers in Cardiovascular Medicine, 2021)
We present the case of a young male patient with an initial diagnosis of a rhabdomyoma that was surgically treated at a different hospital when he was 17. After a 2-year disease-free period, the patient presented another intra-cardiac mass. He refused surgical treatment and died 5 years later. Post-mortem immunochemistry studies of both tumors led to the diagnosis of a primary malignant cardiac PEComa with histopathologic characteristics that resembled a rhabdomyoma with abundant “spider cells.”